The Maqāṣid-Based Analysis of Surah Luqman Verses 12–15: A Study of Ibn ‘Āshūr’s Interpretation in Al-Taḥrīr wa al-Tanwīr - Abdul Rofi Amrullah; Sugeng Wanto (IJoIS: Indonesian Journal of Islamic Studies, 2026)
This study aims to analyze Muḥammad al-Ṭāhir Ibn ‘Āshūr’s interpretation of Surah Luqman verses 12–15 and to uncover the maqāṣid values embedded within these verses in the context of Islamic character formation. The study is motivated by the need for an exegetical approach that not only emphasizes textual aspects but also reveals the objectives of Islamic law (maqāṣid al-sharīʿah) underlying the educational messages of the Qur’an. This research employs a qualitative approach using library research and an interpretative analytical design. Primary data were obtained from Tafsīr al-Taḥrīr wa al-Tanwīr, while secondary data were drawn from literature on Qur’anic exegesis, maqāṣid al-sharīʿah, and relevant academic studies. Data were collected through documentation techniques and analyzed using content analysis with a maqāṣid-oriented approach. The findings indicate that Ibn ‘Āshūr’s interpretation of Surah Luqman verses 12–15 constructs a systematic framework of character formation through the values of tawḥīd (monotheism), gratitude, birr al-wālidayn (filial piety), moral responsibility, discipline in worship, social concern, and humility. The maqāṣid analysis demonstrates that these values are directed toward the preservation of religion, intellect, life, lineage, and social welfare. These findings affirm that Luqman’s advice is not merely normative in nature but also possesses a teleological dimension that remains relevant to contemporary educational challenges. This study contributes to the development of maqāṣid-based Qur’anic Studies and opens avenues for further empirical research on the implementation of Qur’anic values within modern educational contexts.